The First Record of Linguatula serrata Infection of Two-Humped Camel (Camelus bactrinus) In Iran - H Haddadzadeh; S Shamsadin Athari; B Hajimohammadi (Iranian Journal of Parasitology, 2009)
Linguatula serrata, is a cosmopolitan zoonotic parasite. Adult of L. serrrata parasitize the nasopharynx of canids. Consuming raw glandular material of infected intermediate hosts (camel, sheep, cattle, goat, etc.) can infect human. In Iran, two-humped camel is merely found in cold regions (Ardabil and East Azarbijan provinces) and is in danger of extinction. A seven-year-old two-humped male camel, due to car accident injury was sent to slaughterhouse of Tabriz, Iran. In meat inspection practice, the visceral organs were taken out. A small red nodule having a white center was observed at the surface of the left lobe of lung. To study more, the whole of the left lobe of lung was sent to the parasitology laboratory. One nymph of L. serrata was separated from the specimen. This is the first report of infection with L. serrate of two-humped camel in Iran.